The deepest dye : Obeah, Hosay, and race in the Atlantic world - Khan, Aisha, 1955- (Harvard University Press, 2021)
"Aisha Khan examines two cultural phenomena of colonized laborers in the West Indies: the "African" supernatural practice of obeah and the "Indian" mourning festival of Hosay. The British criminalized both, establishing hierarchies through racial and religious identities still relevant to postcolonial power dynamics, as well as justice movements"--